Protection of Rights of Minor Victims of Torture, Inhuman or Degrading: Treatment, or Punishment under the European Convention on Human Rights - Czepek, Jakub (PRAWO i WIĘŹ, 2023)
The author presents research to analyze the particular protection of underaged victims of torture and illtreatment under the European Convention on Human Rights (ECHR). This particularly vulnerable group is entitled to special protection due to its status and susceptibility to various types of abuse. ECHR had the opportunity to analyze the applications concerning violations of the prohibition of torture, inhuman or degrading treatment or punishment concerning minors, among other things, domestic violence, migration, corporal punishment, or sexual abuse. The states parties have particular obligations in this respect due to the nature of the violation and the specific vulnerability of the victim. The purpose of the Article is to focus on minor victims of torture in the context of their particular vulnerability and protection of their respective rights under the ECHR system.